WRITING PATTERNS DEVELOPMENT WITH FOLKLORE IN MODERN FANTASY LITERATURE - Hilma Mufidah; Yosi Wulandari (JLER (Journal of Language Education Research), 2022)
This research was conducted on the curiosity of researchers related to the difficulty of finding studies and discussions of fantasy literature subject. That's why researchers tried to start research to prove fantasy literature could be created from developing local myth, especially, studies related to it are rarely found. The method chosen here is a qualitative descriptive comparative literary approach using intertextual theory by comparing webtoon 7 Wonders that developed its setting on the basis of Nawang Wulan figure from folklor "The Legend of Jaka Tarub" with popular culture concepts such as "Lucifer the Fallen Angel" and "Nyi Roro Kidul". From the development was created a characterization setting. On the other hand, Omnicient Readers developed his work with the dokkaebi and Bihyeong figure of "Lady Dohwa and Banchelor Bihyeong" against the concept of post-apocalypse world, gods, and stream channel or network as target of creating a new world setting in the story. From the conclusions obtained in the result of two works, it can be known that myth such as folklore proved can be made as a reference to fantasy literature.